The impact of comorbidity on cancer and its treatment. (17th February 2016) - Sarfati, Diana; Koczwara, Bogda; Jackson, Christopher
Abstract : Answer questions and earn CME/CNE Comorbidity is common among cancer patients and, with an aging population, is becoming more so. Comorbidity potentially affects the development, stage at diagnosis, treatment, and outcomes of people with cancer. Despite the intimate relationship between comorbidity and cancer, there is limited consensus on how to record, interpret, or manage comorbidity in the context of cancer, with the result that patients who have comorbidity are less likely to receive treatment with curative intent. Evidence in this area is lacking because of the frequent exclusion of patients with comorbidity from randomized controlled trials. There is evidence that some patients with comorbidity have potentially curative treatment unnecessarily modified, compromising optimal care. Patients with comorbidity have poorer survival, poorer quality of life, and higher health care costs. Strategies to address these issues include improving the evidence base for patients with comorbidity, further development of clinical tools to assist decision making, improved integration and coordination of care, and skill development for clinicians.CA Cancer J Clin 2016;66:337‐350. © 2016 American Cancer Society.